2013
DOI: 10.1017/jns.2013.19
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor and megalin gene polymorphisms are associated with central adiposity status and changes among US adults

Abstract: We examined longitudinal associations of vitamin D receptor (VDR) and megalin (LRP2; LDL receptor-related protein-2) gene polymorphisms with central adiposity. We used data from the Baltimore Longitudinal Study of Aging (BLSA), an ongoing prospective open cohort study. Study participants consisted of non-Hispanic white adults residing in Baltimore city, with one or more visits at age ≥50 years, and complete data (n 609–617). Repeated assessments on waist circumference (WC) and waist:hip ratio (WHR) were availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…Other elements in the vitamin D metabolism are the endocytic receptors megalin and cubulin, which are present in the renal tubuli cells [43] and enable transportation of the DBPvitamin D complexes and other filtered proteins into the cells [26]. Cubilin dysfunction may lead to urinary loss of vitamin D in the urine and cause abnormal metabolism of 25(OH)D [44], and MEGALIN polymorphisms are associated with adiposity [45]. Furthermore, an interaction between CUBILIN SNPs and serum 25(OH)D level was also described by Levin et al [25].…”
Section: Discussionmentioning
confidence: 99%
“…Other elements in the vitamin D metabolism are the endocytic receptors megalin and cubulin, which are present in the renal tubuli cells [43] and enable transportation of the DBPvitamin D complexes and other filtered proteins into the cells [26]. Cubilin dysfunction may lead to urinary loss of vitamin D in the urine and cause abnormal metabolism of 25(OH)D [44], and MEGALIN polymorphisms are associated with adiposity [45]. Furthermore, an interaction between CUBILIN SNPs and serum 25(OH)D level was also described by Levin et al [25].…”
Section: Discussionmentioning
confidence: 99%
“…We entered dietary potential confounders that were linked to depression based on previous studies and included vitamins B-6, folate and B-12, total carotenoids (α-carotene, β-carotene, β-cryptoxanthin, lutein+zeaxanthin, lycopene), vitamin C and α-tocopherol 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 (all divided by total energy intake and expressed per 1000 kcal) and the ratio of n-3 polyunsaturated fatty acid (PUFA):n-6 PUFA. 55 Total energy intake was entered as a covariate to emulate a multivariate nutrient density model. 56 Models also included overall dietary quality as measured by the Healthy Eating Index (HEI-2010) total score, with details provided by the National Cancer Institute's Applied Research ( http://appliedresearch.cancer.gov/tools/hei/tools.html ) and the HANDLS ( http://handls.nih.gov/06Coll-dataDoc.htm ) websites.…”
Section: Methodsmentioning
confidence: 99%
“…The complex made of VDR and 1,25(OH) 2 D 3 modulates transcription of vitamin D responsive genes 12 and influences adipocyte differentiation 13 . The effect of VDR gene polymorphism can potentially be sex-specific as shown in at least one previous study with adiposity phenotypes 14 .…”
Section: Introductionmentioning
confidence: 93%
“…Epidemiological studies have confirmed associations of VDR polymorphisms with adiposity and other metabolic disturbances 6 , 14 – 23 . However, studies specifically examining adiposity outcomes either had small sample sizes (<400), (e.g 15 , 16 , 24 .)…”
Section: Introductionmentioning
confidence: 97%